2014
DOI: 10.1080/00140139.2014.980336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of height and load weight on shoulder muscle work during overhead lifting task

Abstract: Few musculoskeletal models are available to assess shoulder deeper muscle demand during overhead lifting tasks. Our objective was to implement a musculoskeletal model to assess the effect of lifting height and load on shoulder muscle work. A musculoskeletal model scaled from 15 male subjects was used to calculate shoulder muscle work during six lifting tasks. Boxes containing three different loads (6, 12 and 18 kg) were lifted by the subjects from the waist to shoulder or eye level. After optimisation of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…During arm elevation, shoulder muscles are highly requested to maintain joint stability, and having an adequate muscle activation pattern plays a major role in the prevention of injuries [18]. To the best of our knowledge, only two studies have identified the effects of arm elevation and weight lifting on muscle activation during simulated working tasks [19,20]. However, the effect of shoulder range of motion was not accounted for, which can be an important contributing factor to shoulder pain of manual handling workers.…”
Section: Introductionmentioning
confidence: 99%
“…During arm elevation, shoulder muscles are highly requested to maintain joint stability, and having an adequate muscle activation pattern plays a major role in the prevention of injuries [18]. To the best of our knowledge, only two studies have identified the effects of arm elevation and weight lifting on muscle activation during simulated working tasks [19,20]. However, the effect of shoulder range of motion was not accounted for, which can be an important contributing factor to shoulder pain of manual handling workers.…”
Section: Introductionmentioning
confidence: 99%
“…We used an OpenSim generic model of the shoulder adapted to lifting task investigation (fully described in [ 9 ]) which was based on a combination of previous Opensim models [ 31 33 ]. Briefly the model was composed of 9 segments and 22 degrees-of-freedom and actuated by 22 muscle-tendon units (including 47 lines of actions with the muscle properties described in [ 34 ]) and 22 residual torque actuators (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The generic model was scaled to match each subject’s anthropometry using the experimental positions of the skin markers during a static pose. In addition, muscle maximal isometric forces were optimized for each subject-scaled-model by minimizing the difference between the normalized EMG and simulated muscle activations obtained during the lifting movement according to the method developed by Blache et al [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations